2022
DOI: 10.3389/fnins.2021.762439
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine String Protein Controls Two Routes of Export for Misfolded Huntingtin

Abstract: Extracellular vesicles (EVs) are secreted vesicles of diverse size and cargo that are implicated in the cell-to-cell transmission of disease-causing-proteins in several neurodegenerative diseases. Mutant huntingtin, the disease-causing entity in Huntington’s disease, has an expanded polyglutamine track at the N terminus that causes the protein to misfold and form toxic intracellular aggregates. In Huntington’s disease, mutant huntingtin aggregates are transferred between cells by several routes. We have previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Upon resveratrol-mediated inhibition of CSPα, the mHtt-EV export was reduced significantly. 122 Thus, CSPα can be a potential therapeutic target for HD. Whether the mHtt-expressing cells use CSPα to decrease the load burden as a survival mechanism is a question of interest as the authors did not report neurotoxicity in the donor mHtt positive and the recipient cells.…”
Section: Huntington's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Upon resveratrol-mediated inhibition of CSPα, the mHtt-EV export was reduced significantly. 122 Thus, CSPα can be a potential therapeutic target for HD. Whether the mHtt-expressing cells use CSPα to decrease the load burden as a survival mechanism is a question of interest as the authors did not report neurotoxicity in the donor mHtt positive and the recipient cells.…”
Section: Huntington's Diseasementioning
confidence: 99%
“…They identified the molecular chaperone, cysteine string protein (CSPα/DnaJC5) carrying EVs, which facilitates the export of disease-causing-polyglutamine-expanded mHtt cargo. Upon resveratrol-mediated inhibition of CSPα, the mHtt-EV export was reduced significantly . Thus, CSPα can be a potential therapeutic target for HD.…”
Section: Role Of Evs In Brain Disorders: Involvement In Pathogenesis ...mentioning
confidence: 99%
“…In the absence of CSPα/DnaJC5, mice, drosophila and C. elegans undergo rapid neurodegeneration, underscoring the essential nature of CSPα/DnaJC5 export in the maintenance of functional neurons (Zinsmaier et al, 1994, Fernandez-Chacon et al, 2004, Kashyap et al, 2014. The evidence supporting CSPα/DnaJC5-mediated export of proteins is substantial (Wu et al, 2023, Deng et al, 2017, Fontaine et al, 2016, Pink et al, 2021. CSPα/DnaJC5 is found in cell-derived lipid bilayer enclosed particles, called extracellular vesicles (EVs) (Deng et al, 2017, Pink et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence supporting CSPα/DnaJC5-mediated export of proteins is substantial (Wu et al, 2023, Deng et al, 2017, Fontaine et al, 2016, Pink et al, 2021. CSPα/DnaJC5 is found in cell-derived lipid bilayer enclosed particles, called extracellular vesicles (EVs) (Deng et al, 2017, Pink et al, 2021. While some EVs are directly formed and released from the plasma membrane, other vesicles are first generated through endosomal, multivesicular bodies that subsequently fuse with the plasma membrane and release their internal vesicles into the extracellular milieu (Pegtel andGould, 2019, Cheng andHill, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other disease-causing toxic misfolded proteins are exported from neurons through vesicle secretion, reinforcing the idea of an off-site disposal strategy [ 68 ]. For instance, Braun’s group demonstrated that both mutant superoxide dismutase-1 and polyglutamine-expanded HTT are exported via EVs from catecholaminergic derived CNS cells, with the help of the molecular chaperone CSPα [ 69 ]. Moreover, neuronal exosomes have been reported to facilitate conformational change of extracellular Aβ into nontoxic amyloid fibrils and promote its internalization by microglia for degradation [ 70 ].…”
Section: Introductionmentioning
confidence: 99%